On optimal stopping of Markov processes - Grigelionis, B. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Григелионис. Об оптимальной остановке марковских процессов B. Grigelionis. Apie Markovo procesų optimalų sustabdymą